PO.5.101 The effect of belimumab on renal outcomes in a pre-specified subgroup analysis of a phase 3 randomised trial in a european population with lupus nephritis. (27th September 2022) - Andreoli, L; Amoura, Z; Morales, E; Jones-Leone, A; Levy, RA; Gilbride, JA; Carnarius, H; Korsten, P
Abstract : Purpose: To evaluate the efficacy and safety of intravenous (IV) belimumab (BEL) in the European subgroup of patients with lupus nephritis (LN) from the previously published BLISS-LN study.1 Methods: BLISS-LN was a Phase 3, double-blind, placebo (PBO)-controlled 104-week study (GSK Study BEL114054; NCT01639339 ). Adult patients with biopsy-proven LN (class III, IV, and/or V) were randomised (1:1) to receive monthly BEL 10 mg/kg IV or PBO, plus standard therapy for LN (cyclophosphamide/azathioprine [CYC/AZA] or mycophenolate mofetil [MMF]). The primary endpoint was primary efficacy renal response (PERR: urine protein/creatinine ratio [uPCR] ≤0.7, estimated glomerular filtration rate [eGFR] no more than 20% below the pre-flare value or ≥60 ml/min/1.73 m2, no rescue therapy) at Week 104; secondary endpoints included complete renal response (CRR: uPCR <0.5, eGFR no more than 10% below the pre-flare value or ≥90 ml/min/1.73 m2, no rescue therapy) at Week 104 and time to renal-related event (end-stage renal disease/doubling of serum creatinine from baseline/renal worsening/renal disease-related treatment failure) or death. The subgroup analyses reported here were pre-specified, except for time to renal-related event or death (post hoc), and are descriptive. Results: Out of the overall population (N=448), the European subgroup comprised 86 patients (19.2%; PBO, n=45; BEL, n=41) from Belgium, the Czech Republic, France, Germany, Hungary, the Netherlands, the Russian Federation, Spain and the United Kingdom. Compared with the PBO group, more patients in the BEL group had nephrotic range proteinuria, and longer disease duration (both LN and systemic lupus erythematosus [SLE]) at baseline ( Table 1 ). Overall, more patients received CYC/AZA than MMF induction therapies ( Table 1 ). Both PERR and CRR had numerical trends in favour of BEL compared with PBO at Week 104 ( Table 2 ), which was consistent with the results of the overall study population. 1 Belimumab reduced the risk of renal-related event or death over time by 48% compared with PBO ( Table 2 ). Consistent with the overall study population, almost all patients reported at least one adverse event, regardless of treatment group (PBO, n=44 [97.8%]; BEL, n=39 [95.1%]). Conclusions: Greater improvements in renal outcomes were seen in favour of BEL compared with PBO; as expected in a small subgroup, these were not statistically different. The higher proportion of patients in the BEL group versus the PBO group with baseline nephrotic range proteinuria and longer disease durations may explain why the PERR and CRR results were less pronounced in the European subgroup than the overall population. These results should be interpreted cautiously due to the inherent limitations of a subgroup analysis and the small sample sizes. References: Furie R, et al. N Engl J Med . 2020;383 :1117–28 Funding: GSK